A Consistent Framework for Coupling Basal Friction With Subglacial Hydrology on Hard‐Bedded Glaciers. Issue 13 (8th July 2022) - Gilbert, Adrien; Gimbert, Florent; Thøgersen, Kjetil; Schuler, Thomas V.; Kääb, Andreas
Abstract: Below hard‐bedded glaciers, both basal friction and distributed subglacial drainage are thought to be controlled by a network of cavities. Previous coupled hydro‐mechanical models, however, describe cavity‐driven friction and hydraulic transmissivity independently, resulting in a physically inconsistent cavity evolution between the two components of the models. Here, we overcome this issue by describing the hydro‐mechanical system using a common cavity‐evolution description, that governs both transient friction and hydraulic transmissivity. We show that our coupling approach is superior to previous formulations in explaining a unique observation record of glacier sliding speed from the French Alps. We find that, at multi‐day to multi‐decadal timescales, sliding speed can be expressed as a direct function of basal shear stress and water discharge, without accounting for water pressure, which simply adjusts to maintain the cavitation ratio needed to accommodate the water supply. Plain Language Summary: Predicting the sliding speed of glaciers and ice sheets is challenged by the difficulties of assessing the water pressure at the glacier base. Here, we improve the coupling between existing theories about basal friction and subglacial hydrology by introducing a consistent description of roughness and hydraulic transmissivity. Our work breaks with the common view on the subglacial environment that water pressure drives the sliding speed by modulating friction at the glacier base. Instead, our findings show that at multi‐day and longer timescales sliding speed and water pressure are imposed by the water discharge along the glacier base that needs to be accommodated. Our results open new perspectives for understanding contemporary glacier and ice sheet sliding and predicting its future behavior under changing climate. Key Points: We introduce a consistent framework to describe the effect of cavitation on both friction and hydraulic transmissivity This approach reduces the number of parameters of the coupled hydro‐mechanical problem and shows better performance in explaining our data We find that seasonal sliding variations are well captured assuming cavities in equilibrium with their average discharge